MicroRNA: role in macrophage polarisation and colorectal cancer pathogenesis - Lin, Haihong; Zhou, Jun; He, Ying; Zhu, Yifan; Chen, Puwen; Yan, Hongwei; Huang, Junyun; Gong, Ersheng; Wang, Xiaoling (Frontiers in Cell and Developmental Biology, 2025)
Colorectal cancer (CRC) represents a highly common gastrointestinal malignancy ranking among the top three most frequently diagnosed cancers in the digestive system. The disease’s high mortality rate makes treatment particularly difficult. As a result, thorough research into the cause and effective treatment of CRC is especially crucial. The macrophage’s remarkable functional flexibility, as a cell with strong immunological effects, allows it to demonstrate both anti-tumor and tumor-inducing activities. MicroRNAs (miRNAs), functioning as short non-protein-coding RNAs, mediate post-transcriptional regulation through mRNA destabilization and translational suppression, and they play a unique function in macrophage formation, polarization processes, and anti-inflammatory activity. Elucidating the crosstalk between miRNA-mediated gene regulation and macrophage functional polarization in CRC pathogenesis constitutes a critical research priority. We first provide a brief overview of the epidemiological of CRC, systematically summarising the origin of macrophages, their physiological functions, and their potential pathogenic mechanisms in colorectal carcinogenesis. Subsequently, we elaborated in depth on the critical role of miRNAs in regulating macrophage polarisation status. Ultimately, this paper comprehensively explores the mechanistic involvement of miRNA-macrophage interactions in CRC progression.